Attitudes towards COVID-19 vaccination: A cross sectional study in the Federal Capital Territory, Nigeria. - Obi Peter Adigwe; Godspower Onavbavba (Public Library of Science (PLoS), 2024)
Vaccine acceptance is complex and context-specific, varying across time, place and perceived behavioural nature of the community involved. A high vaccine acceptance rate is important to achieve herd immunity, however, vaccine hesitancy is a possible barrier to this. This study aimed to assess attitudes towards COVID-19 vaccination and associated factors. A cross-sectional survey was undertaken to investigate the attitudes of Federal Capital Territory residents towards COVID-19 vaccine uptake in Nigeria. Data were collected using questionnaires which were administered to respondents physically and online through random and snowball sampling strategies respectively. Data received were then analysed using Statistical Package for Social Sciences (SPSS). A total of 1767 responses were received with males representing 57.8% of the sample. More than half (54.9%) of the respondents were between the ages of 18-30 years. A third (35.4%) of the study participants indicated that a vaccine was not necessary for COVID-19, and 56.5% indicated willingness to accept COVID-19 vaccination. The majority of the sample (56.9%) indicated that the government decision-making was in their best interest, whilst close to two-thirds of the respondents (61%) were of the view that COVID-19 vaccination should not be made compulsory. Older respondents as represented by those over 60 years were more likely to accept COVID-19 vaccination (p = 0.039). This study however revealed negative attitudes towards COVID-19 vaccination, indicating the urgent need for government, policymakers, and other stakeholders to prioritise the development of strategies that can appropriately address vaccine hesitancy in the study setting. Contextual interventions indicated include strategic public enlightenment campaigns targeting populations with less favourable dispositions towards being vaccinated.